Causas y afectaciones por fenómenos volcánicos en el sistema territorial del Eje Cafetero: insumo para la formulación de indicadores de vulnerabilidad territorial (2016)
This paper is the result of the research project “Retrospective of natural disasters in Colombia as input for the construction of a decision support system” developed by the Geophysical Institute of the Pontificia Universidad Javeriana and the Catholic University of Colombia. The research goal was to build a decision support system which also incorporates response mechanisms in the territory in the short, medium and long term. Three study cases were taken in the regions of Mojana , Armero and Manatí, where major natural disasters occurred. The preliminary results took the coffee area as a study area focusing on the town of Armero, who suffered the total destruction of its territory by a volcano eruption of Nevado del Ruiz in 1985. The region was characterized together with a fieldwork in order to propose a system of indicators of vulnerability in several dimensions and an action plan in case of a volcano eruption. Also, an application for smartphones was proposed in order to teach how to perform a risk management of a volcanic event.